Oxytocin enhances attention to the eye region in rhesus monkeys - Dal Monte, Olga; Noble, Pamela; Costa, Vincent D.; Averbeck, Bruno B. (Frontiers in Neuroscience, 2014)
Human and non-human primates rely on the ability to perceive and interpret facial expressions to guide effective social interactions. The neuropeptide oxytocin (OT) has been shown to have a critical role in the perception of social cues, and in humans to increase the number of saccades to the eye region. To develop a useful primate model for the effects of OT on information processing, we investigated the influence of OT on gaze behavior during face processing in rhesus macaques. Forty-five minutes after a single intranasal dose of either 24IU OT or saline, monkeys completed a free-viewing task during which they viewed pictures of conspecifics displaying one of three facial expressions (neutral, open-mouth threat or bared-teeth) for 5 s. The monkey was free to explore the face on the screen while the pattern of eye movements was recorded. OT did not increase overall fixations to the face compared to saline. Rather, when monkeys freely viewed conspecific faces, OT increased fixations to the eye region relative to the mouth region. This effect of OT was particularly pronounced when face position on the screen was manipulated so that the eye region was not the first facial feature seen by the monkeys. Together these findings are consistent with prior evidence in humans that intranasal administration of OT specifically enhances visual attention to the eye region compared to other informative facial features, thus validating the use of non-human primates to mechanistically explore how OT modulates social information processing and behavior.